Importance of the correct application of budgetary principles in Public Procurement in Colombia. Case of final report of regularity audit Fund of Economic Benefits, Unemployment and Pensions FONCEP contract No. 0062 signed with the Francisco José De Caldas District University (2021)
To talk about public contracting, one would necessarily have to go through the legal obligation that each and every one of the public entities in Colombia have, regarding the fulfillment of public service through the celebration of state contracts, which are framed under the constitution Politics of Colombia (CPC) as supreme norm, the legal contracting statute under Law 80 of 1993 with its regulatory decrees and the public contracting manuals of each entity; The latter, are allowed by virtue of their autonomy, their mission and the regime that each one has, however, they must always be framed under the provisions of the Law. State contracting is based on the Political Constitution of Colombia of 1991, under its Article 2 which establishes “The essential purposes of the State are: to serve the community, promote general prosperity and guarantee the effectiveness of the principles, rights and duties enshrined in the Constitution (...)” (Const., 1991, art. 2). It is for this reason that a tour will be made of two budgetary principles that support and base this analysis, which in financial matters has effects that generate criminal, administrative and fiscal events; hence the great importance of these.